Keberlanjutan Baju Kurung sebagai Warisan Budaya Bagi Perempuan Minangkabau - Silvia Rahmanisa; Solfema Solfema; Lili Dasa Putri (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2025)
Minangkabau culture, which is known for the principle of "Syara' Basandi Adat, Syara' Basandi Kitabullah" has a rich culture, one of which is the traditional costume Baju Kurung Basiba. Apart from functioning to cover the body, this shirt also reflects the identity, honor and cultural values ​​of Minangkabau which are closely related to the Islamic religion. However, as time goes by and the influence of globalization, the use of Baju Kurung Basiba among the younger generation is increasingly fading. This article aims to explore the role and philosophical meaning of Baju Kurung in the social life of Minangkabau society as well as the challenges faced in preserving it in the modern era. Through literature searches, it was found that even though there are big challenges, such as the influence of global fashion trends and the declining interest of the younger generation, there are still opportunities to maintain the existence of Baju Kurung through design innovation and the use of social media, as a promotional tool. Cultural education and social media play an important role in preserving this cultural heritage, so that Baju Kurung can continue to be loved and enjoyed by future generations.